Uncovering the non-radiative thermal characteristics of a passive radiative cooler under real operating conditions. (29th December 2022) - Kocer, Hasan; Durna, Yilmaz; Isik, Halil; Soydan, Mahmut Can; Khalichi, Bahram; Ghobadi, Amir; Kurt, Hamza; Ozbay, Ekmel
Abstract: Passive radiative cooling (PasRadCool), which emits thermal energy from objects to deep cold space through atmospheric transparency, offers complementary and alternative green energy solutions for passive cooling of buildings, clothing, and renewable energy harvesting. Depending on the spectral emissive/absorptive properties of the unit under test (UUT), radiative heat exchanges occur between the UUT, atmosphere, and sun, while at the same time non-radiative heat exchange occurs. The performance of the PasRadCool is determined by the combined thermal and thermodynamic effects of both exchange mechanisms. Although the non-radiative heat exchange, which consists of conductive and convective processes to the outer surfaces of the UUT and the surrounding air fluid, is very sensitive to environmental changes, the actual performance is not fully determined since this feature is considered statically in many studies. Herein, we propose a method that reveals the non-radiative thermal characteristics of the PasRadCool under real operating conditions. With a photonic radiative cooler structure, which we manufacture as a proof of concept, we perform nighttime field test measurements in varying non-radiative thermal conditions. The proposed method extracts the time-dependent non-radiative heat transfer coefficient of the UUT as accurately as possible. We also confirm that our experimental result shows good agreement with both numerical and analytical methods. The proposed approach, which highlights the realistic thermal management of PasRadCool, is not specific to the circumstances of our study and can be applied to all PasRadCool situations with different geometry, material, and environmental conditions.